(untitled) (Quinto Sol, 2018)
In this paper we analyze the university policies taken place throughout the coup d’etat of 1966 under Onganía’s (1966-1970) and Levingston’s (1970-1971) presidencies. Accordingly, we reconstruct the strategies that were implemented during these years in order to build a dialogue with the university youth. We argue that these actions took place after the repression failed. For this purpose, we worked with primary and secondary sources, among which newspapers, journals and presidential speeches stand out.